Extracorporeal shock wave therapy decreases COX‐2 by inhibiting TLR4‐NFκB pathway in a prostatitis rat model. Issue 13 (2nd August 2019) - Jeon, Seung Hwan; Zhu, Guan Qun; Kwon, Eun Bi; Lee, Kyu Won; Cho, Hyuk Jin; Ha, U‐Syn; Hong, Sung‐Hoo; Lee, Ji Youl; Bae, Woong Jin; Kim, Sae Woong
Abstract: Background: This study aims to evaluate the effect of extracorporeal shock wave therapy (ESWT) on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and to explore the mechanism. Methods: RWPE‐2 cells were randomly divided into three groups: (a) RWPE‐2 group (normal control), (b) LPS groups (lipopolysaccharide inducing inflammation) and (c) ESWT groups (LPS induced RWPE‐2 treated by ESWT). After ESWT was administered, cells and supernatant were collected for enzyme‐linked immunosorbent assay (ELISA) and Western blot analysis. In vivo, Sprague‐Dawley rats ( n = 30) were randomly divided into three groups: (a) normal control group, (b) prostatitis groups, and (c) ESWT groups. Prostatitis rats were induced by 17 β‐estradiol and dihydrotestosterone for 4 weeks. After ESWT, prostates of each group were collected for immunohistochemistry, Western blot analysis, and ELISA. Results: ESWT improved prostatitis by attenuating inflammation ( P < .01). ESWT downregulated the expression of cyclooxygenase 2 (COX‐2) through inhibiting TLR4‐NFκB pathway compared with the LPS group in vitro or prostatitis group in vivo ( P < .05). TRAF2 mediates ERK1/2‐COX2 pathway. ESWT promotes prostate tissue recovery by stimulating vascular endothelial growth factor expression ( P < .01). ESWT could suppress apoptosis in the prostate. Conclusions: ESWT improved CP/CPPS and reduced inflammation by degrading COX‐2 in microenvironment through TLR4‐NFκB‐inhibiting pathway. TRAF2 regulator in ERK1/2‐COX‐2 inhibition significantly reduced inflammation, thus suggesting ESWT may be a potential and promising treatment for CP/CPPS.